Hierarquia urbana, estrutura ocupacional e o prêmio salarial à qualificação: decomposição dos determinantes das desigualdades interurbanas de rendimento no Brasil - Gustavo Geaquinto Fontes (2014)
This thesis investigates spatial inequality in Brazilian labour market, analyzing wage disparity along the urban hierarchy and its evolution over the past two decades. The main objective of this study is to investigate the effects of urban hierarchy on the incomes of individuals of different skill levels (as measured by education and experience), as well as the occurrence of different returns, along the urban hierarchy, to jobs of different task categories (cognitive occupations, routine non-manual and manual occupations). Therefore, the thesis sought to identify the existence of an urban wage premium not only to education and experience, but also to more skilled and knowledge-intensive jobs, in order to highlight the role of occupational insertion of individuals in wage determination and the importance of the urban hierarchy in this process. In Brazil, the analyzed period was characterized by an improvement of the educational level of the countrys workforce, an advance of the process of demographic transition and a major restructuring of the productive sectors, which led to a relative spatial de-concentration of the manufacturing industrial production and changes in the balance of local comparative advantages. Considering the strong shifts in supply and demand for labor in the past two decades, in order to better understand the spatial dimension of the wage determination process, in this thesis we sought to incorporate into regional and urban analysis some theoretical frameworks in the field of labor economics, especially models that attribute the role of tasks and occupations as a key element in explaining the recent changes in the wage structure. For this purpose, we employed different decomposition methods, which enabled to identify the main determinants of intercity differentials in labor income, not only average differentials, but also at different points of the wage distribution curve. We used micro-data of Brazilian Census from the years 1991, 2000 and 2010, which enabled the coverage of the countrys entire territory. Among the main results, we identified an important urban wage premium for the most qualified individuals with higher levels of education and experience and particularly for workers employed in cognitive tasks living in large urban centers. Furthermore, it was observed that during the period there was an intensive reduction of interurban inequalities at the intermediate levels of the wage curve, remaining, however, strong differences at the top of the distribution. Finally, for better understanding the wage determination process and the distributional changes over time and over space, this thesis proved to be essential to incorporate in the analysis elements that go beyond the usual measures of skill (education and experience), especially variables related to job tasks and occupations.